10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
Using latent profile transition analysis, this study identified patterns and developmental changes in adolescents' coping across high school prior to COVID-19 and examined whether pre-pandemic coping differentiated depressive symptom trajectories across the pandemic years as youth transitioned into emerging adulthood. Participants were a diverse cohort (N = 940; 51% female; 34% White, 26% Latinx, 15% Multi-racial and multi-ethnic) assessed annually in Grades 9-12 on 5 coping indicators (internalizing, externalizing, social support seeking, problem solving, and avoidance). Distinct coping profiles reflected relatively approach-oriented coping (Balanced; Regulated Approach) and more avoidant or reactive coping (Reactive Approach; Self-Directed). A low-engagement, self-directed profile emerged in Grade 9 and, by Grade 10, differentiated into Balanced or Self-Directed patterns. Profile transitions were most evident early in high school and became stabilized thereafter. With this later stability, Grade 12 coping patterns differentiated depressive symptom trajectories across the COVID-19 pandemic (2021-2023). Specifically, Balanced and Regulated Approach (i.e., approach-oriented) profiles had fewer depressive symptoms, whereas Reactive Approach and Self-Directed (i.e., avoidant, reactive) profiles had more depressive symptoms. Findings highlight both continuity and early reorganization in coping across adolescence and show that coping -pathways foreshadowed depressive symptom trajectories during the pandemic as youth transitioned into emerging adulthood.